Feasibility to estimate mean systemic filling pressure with inspiratory holds at the bedside - Wijnberge, Marije; Jansen, Jos R. C.; Pinsky, Michael R.; Klanderman, Robert B.; Terwindt, Lotte E.; Bosboom, Joachim J.; Lemmers, Nikki; Vlaar, Alexander P.; Veelo, Denise P.; Geerts, Bart F. (Frontiers in Physiology, 2022)
Background: A decade ago, it became possible to derive mean systemic filling pressure (MSFP) at the bedside using the inspiratory hold maneuver. MSFP has the potential to help guide hemodynamic care, but the estimation is not yet implemented in common clinical practice. In this study, we assessed the ability of MSFP, vascular compliance (Csys), and stressed volume (Vs) to track fluid boluses. Second, we assessed the feasibility of implementation of MSFP in the intensive care unit (ICU). Exploratory, a potential difference in MSFP response between colloids and crystalloids was assessed. Methods: This was a prospective cohort study in adult patients admitted to the ICU after cardiac surgery. The MSFP was determined using 3–4 inspiratory holds with incremental pressures (maximum 35 cm H2O) to construct a venous return curve. Two fluid boluses were administered: 100 and 500 ml, enabling to calculate Vs and Csys. Patients were randomized to crystalloid or colloid fluid administration. Trained ICU consultants acted as study supervisors, and protocol deviations were recorded. Results: A total of 20 patients completed the trial. MSFP was able to track the 500 ml bolus (p < 0.001). In 16 patients (80%), Vs and Csys could be determined. Vs had a median of 2029 ml (IQR 1605–3164), and Csys had a median of 73 ml mmHg−1 (IQR 56–133). A difference in response between crystalloids and colloids was present for the 100 ml fluid bolus (p = 0.019) and in a post hoc analysis, also for the 500 ml bolus (p = 0.010). Conclusion: MSFP can be measured at the bedside and provides insights into the hemodynamic status of a patient that are currently missing. The clinical feasibility of Vs and Csys was judged ambiguously based on the lack of required hemodynamic stability. Future studies should address the clinical obstacles found in this study, and less-invasive alternatives to determine MSFP should be further explored. Clinical Trial Registration:ClinicalTrials.gov Identifier NCT03139929.